The ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL CERITA SPLDV BERDASARKAN TAHAPAN NEWMAN DITINJAU DARI TIPE KEPRIBADIAN FLORENCE LITTAUER - Santoso, Mutiara Winda; Trapsilasiwi, Dinawati; Murtikusuma, Randi Pratama (Department of Mathematics Education , University of Jember, 2021)
The aim of this qualitative research is to describe the types of student errors in solving the two-variable linear equation system story problem based on Newman's error analysis in terms of Florence Littauer's personality type. The data sources consisted of 8 students of grade IX C SMP Nuris Jember who had been taught the material of two-variable linear equation systems. The data taken were the results of the questionnaire used to group students into four categories of personality types, the results of the student's story problem solving test results, and the results of the interviews of the students who were the research subjects. The results showed that in solving the two-variable linear equation system material story problems, students sanguinis experienced reading errors, comprehensior errors, transformation errors, process skill errors, and encoding error. Melancholy and phlegmatis students experience transformation error, process skill error, and encoding error. Koleris students experienced process skill error and encoding error. Keywords: Error, Newman, Personality Type, SPLDV